KONSEP PEMBELAJARAN AKTIF, INOVATIF, KREATIF, EFEKTIF, DAN MENYENANGKAN (PAIKEM) - Ara Hidayat (AN NUR: Jurnal Studi Islam, 2012)
The important key of implementation of good learning is the presence of situation of active, innovative, creative, effective and enjoyable learning or what is commonly known as PAIKEM. Learning is relates to how to make a student can learn easily and how to create motivation for student to study the lesson in accordance with the expected goals. In learning, practitioners of education are required to develop a variety of methods and strategies to achieve the goals of learning, so it can be achieved in an effective, efficient and enjoyable learning. The PAIKEM learning model is intended as a learning tool or method to achieve maximum, effective, and efficient outcomes of learning. PAIKEM learning model is firstly known by the end of 2007 coinciding with the Implementation of the Profession Training and Education (PLPG) for teachers who have not passed certification through portfolio assessment.